Semiotic Consequences - Jonathan Culler (Studies in 20th & 21st Century Literature, 1981)
This paper outlines the semiotic perspectives of Saussure and Peirce and the points at which these quite different theories intersect. It considers the implications of these points of intersection for literary studies and uses the example of Oedipus Rex to illustrate the semiotic character of acts and facts.
Keywords: Saussure; Peirce; Oedipus Rex; acts; facts; semiotics; intellect; philosophy